Thermal Model in ANSYS for a Comparison Between two Configurations of a Concentrating Photovoltaic System. Issue 11 (3rd July 2019) - Renno, Carlo; Petito, Fabio; Accarino, Maurizio Luigi
ABSTRACT: The theoretical analysis of different concentrating photovoltaic and thermal systems (CPV/T) is presented in this paper; it allows to evaluate the cooling fluid temperature in different working conditions. In particular, two CPV/T systems with different optics, line-focus and point-focus, are studied and compared theoretically by means of a model developed in ANSYS-CFX able to evaluate the theoretical temperature values of the fluid that flows in the cooling circuit, designed with the Solidworks software. The comparison in terms of the thermal performances between the point-focus and line-focus configurations of a CPV/T system has been realized considering different working conditions. As model input the uniform cell temperature has been set to different values, included between 323 K and 363 K, or determined experimentally referring to the point-focus configuration. In particular, the outlet temperatures of the cooling fluid, the fluid and cells temperatures difference at the outlet section, the time necessary to reach a steady-state condition, the fluid temperature trend in different parts of the tube and along the circuit, have been evaluated. Moreover, the fluid temperature trend has been studied varying the fluid velocity, its mass flow rate, and the insulation thickness. Finally, the point-focus CPV/T system thermal performances have been also evaluated adopting some experimental measurements as input data; the fluid temperature trend has been tested under a variable cell temperature during different hours of a sunny and a cloudy day.